HUBUNGAN ANTARA KEPUASAN PERNIKAHAN DENGAN KASIH SAYANG ORANGTUA PADA ANAK DENGAN AUTISM SPECTRUM DISORDER - Nanda Faradiza Jolanet Adam; Hartanti; Mary Philia Elisabeth (Perpustakaan Universitas Surabaya, 2021)
Abstract – Understanding the awareness of the Indonesian public regarding children who have autism spectrum disorder (ASD) can be said that very minimal. The lack of understanding and awareness can influence a person's behavior, especially parents in their children who have ASD. Children who have ASD will find it difficult to do social activities in their environment. Couples who are often involved in debates in their married life are likely to influence satisfaction in their marriages. In this study, researchers wanted to see the relationship between marital satisfaction with parental affection for their ASD child. Subjects were taken as many as 202 parents (104 women, 90 men, 8 others) by accidental sampling who had ASD children and still had